Effects of wild plant essential oils in the growth control of Phytophthora cinnamomi abd the host Castanea sativa Mill - Guimarães, Rafaela (2011)
Plant diseases caused by this genus are difficult to control chemically, and the perspective of a active natural product agent as a great importance especially in regions that have chestnut as main natural resource. The essential oils are natural compounds with bactericide, fungicide and allelopathic effects, this characteristics can be a very interesting tool to fifth or control the infections produced by Phytophthora cinnamomi. Essential oils from wild plants growing in the northeast region of Portugal were tested in vitro in is effects on the growth of Phytophthora cinnamomi.The essential oils were tested in differents concentrations from 100% to 2%. Dilutions were madewith alcohol 10%, and were tested in mycelium after 1,2,3, and 4 weeks in culture. Simultaneously in vitro chestnut plants were tested in they growth in the present of imbibed paper filter with the same essential oils and concentrations in order to understand if the essential oils can affect the development of the plants.Preliminary show that essential oils from plants of Mentha genus can reduce the P. cinnamomi growing without affect drastically the C. sativa in vitro development.